PHYSICAL SOIL C CHARACTERISTICS OF WATERLOGGED AND SALINE LANDS OF FIVE DISTRICTS OF HARYANA, INDIA - Raizada, S.; Chadha, N. K.; Hasan, Javed; Maheshwari, U. K. (Journal of Indian Fisheries Association, 2015)
Physical characteristics of waterlogged and saline soils of five districts, namely Rohtak, Faridabad, Gurgaon, Sonipat and Jhajjar, of Haryana were studied to evaluate the aquaculture potential. The soil samples from 76 sites were procured and analysed for pH, electrical conductivity, soil particles and water retention capacity, since the knowledge of these parameters is essential for the preliminary evaluation of a site for aqua-farming. Six soil types were identified and clay-loam was observed to be the maximum at 45 (59.21%) sites, followed by silty-clay loam at 14 (18.42%), sandy-clay loam at six (7.89%), silty-loam at four (5.26%), sandy-loam at four (5.26%) and loam at three (3.94%) sites. The pH of soil indicated moderate to high alkaline conditions ranging between 8.01and 9.00 at 53 (69.73%) sites, 9.01 and 10.00 at 17 (22.36%) sites, and low between 7.01 and 8.00 at six (7.89%) sites. The electrical conductivity was found to range between <1 and 10 mmho cm -1 with the value of <1.0 mmho cm -’ at 36 (47.36%) sites. The water retention capacity was observed mostly to be moderate. The paper describes the interrelationship between these parameters with reference to the suitability for aqua-farming. Keywords: Soil survey, aqua-farming, soil particles, pH, electrical conductivity, water retention capacity